Enhancement of constructability concept: An experience in offsite Malaysia construction industry - Mohd Nawi, Mohd Nasrun; Mohamad Kamar, Kamarul Anuar; Abdullah, Mohd Rodzi; Haron, Ahmad Tarmizi; Lee, Angela; Arif, Mohammed (2009)
﻿In the construction process of a traditional contracting system, most design drawings and specifications that produced by the design engineers are tend to be performance oriented, specifying an end result and materials, while leaves the means and methods for constructing the work to the contractor. While in nature, A/Es are not exactly expert in construction means and method.Consequently, the reality of construction is that most of the problems encountered in the field such as reworks, delay and low in quality or productivity are often compounded by inherent design flaws that generated in the design phase. An alternative solution to overcome the problem is by implementing of constructability concept. Constructability is often portrayed as integrating construction knowledge, resource, technology and experience into the engineering and design of a project.Since 1998, government Malaysian through Construction Industry Development Board (CIDB) seriously took an action to reform the current construction practice (currently use conventional method) towards industrialization concept. One of the main strategies had been taken by the government which introduced a concept of design of prefabrication, pre-assembly and modularization especially in public projects. This paper will highlight the initiative have be done by in the Malaysian construction industry to implement that system and indirectly the concept of constructability will be enhanced.